Anti-inflammatory and toxicological evaluation of essential oil from Piper glabratum leaves - Branquinho, Lidiane Schultz; Santos, Joyce Alencar; Cardoso, Claudia Andrea Lima; Mota, Jonas da Silva; Junior, Ubirajara Lanza; Kassuya, Cândida Aparecida Leite; Arena, Arielle Cristina [UNESP] (Elsevier, 2017)
Ethnopharmacological relevance Although some of the species of the genus Piper exhibit interesting biological properties, studies on Piper glabratum Kunth are very limited. Aim of the study This study investigated the anti-inflammatory activity and the toxicological profile of the essential oil from P. glabratum leaves (OEPG) in mice. Materials and Methods The acute toxicity of OEPG was evaluated by oral administration to female mice as single doses of 500, 1000, 2000 or 5000 mg/kg/body weight. In the subacute toxicity test, the females received 500 or 1000 mg/kg/body weight of OEPG for 28 days. The anti-inflammatory potential of OEPG was evaluated using four models including pleurisy, edema, mechanical hyperalgesia and cold allodynia models in mouse paws. Results No clinical signs of toxicity were observed in animals after acute treatment, which suggested that the LD50 is greater than 5000 mg/kg. The subacute exposure to OEPG produced no significant changes in the hematological or biochemical parameters. Similarly, the histology of the organs and the estrus cycle displayed no marked alterations. OEPG exhibited anti-inflammatory activity as indicated by inhibition of the leukocyte migration (100, 300, 700 mg/kg) and the protein extravasation into the pleural exudates (700 mg/kg). After intraplantar injection of carrageenan, it was observed that the 700 mg/kg dose of OEPG reduced edema formation and decreased the sensitivity to mechanical stimulation and cold. Conclusions These results demonstrate the anti-inflammatory potential of the essential oil of P. glabratum leaves in the absence of toxicity in female mice.
Keywords: Carrageenan; Essential oil; Inflammation; Piper glabratum; Toxicity